Pourquoi des noms ne sont pas des attributs - Soskice, Janet Martin 1951- (2018)
Depuis de nombreuses décennies, et même depuis plusieurs siècles, les approches philosophiques sur la nature de Dieu ont été dominées par la discussion des « attributs divins » – toute-puissance, omniscience, etc. Le présent article suggère que cette tradition a perdu sa légitimité et qu’il nous faut recouvrer ces prédicats dans leur contexte plus ancien en tant que « noms divins » – l’approche habituelle pour la discussion de la nature divine, de la théologie ancienne jusqu’à la première modernité.
For many decades, even several centuries, philosophical treatments of God’s nature have been dominated by discussion of the so-called “divine attributes” – omnipotence, omniscience, and so on. This article suggests that this tradition is bankrupt and that we need to recover these predicates in their earlier context as “divine names” – the standard locus for the discussion of the divine nature through the early modern period. This, in turn, takes us back to the doctrine of creatio ex nihilo and the understanding of Philo and theologians of the early Church that, strictly speaking, God is unnameable, the I AM from which all things have their being, and revelation the source of our naming. Christ is this “I AM”.